Educação em saúde a partir da produção de histórias em quadrinhos: guia didático - Belém, Josiana Ferreira (Brasil, 2024)
This product originates from the dissertation entitled "Comic stories: a didactic alternative for teaching and learning about diseases caused by helminths", developed in the Postgraduate Program in Technological Education - PPGET, of the Federal Institute of Education, Science and Technology of Amazonas, with the aim of assisting and encouraging health education in the classroom through the use and production of comic books, as a didactic alternative in the process of teaching and learning content related to diseases caused by helminths. In this proposal, the contents refer to three diseases caused by helminths, ascariasis, hookworm and enterobiasis.